Harnessing CD8+ T Cells Under HIV Antiretroviral Therapy - Warren, Joanna A.; Clutton, Genevieve; Goonetilleke, Nilu (Frontiers in Immunology, 2019)
Antiretroviral therapy (ART) has transformed HIV from a fatal disease to a chronic condition. In recent years there has been considerable interest in strategies to enable HIV-infected individuals to cease ART without viral rebound, either by purging all cells infected harboring replication-competent virus (HIV eradication), or by boosting immune responses to allow durable suppression of virus without rebound (HIV remission). Both of these approaches may need to harness HIV-specific CD8+ T cells to eliminate infected cells and/or prevent viral spread. In untreated infection, both HIV-specific and total CD8+ T cells are dysfunctional. Here, we review our current understanding of both global and HIV-specific CD8+ T cell immunity in HIV-infected individuals with durably suppressed viral load under ART, and its implications for HIV cure, eradication or remission. Overall, the literature indicates significant normalization of global T cell parameters, including CD4/8 ratio, activation status, and telomere length. Global characteristics of CD8+ T cells from HIV+ART+ individuals align more closely with those of HIV-seronegative individuals than of viremic HIV-infected individuals. However, markers of senescence remain elevated, leading to the hypothesis that immune aging is accelerated in HIV-infected individuals on ART. This phenomenon could have implications for attempts to prime de novo, or boost existing HIV-specific CD8+ T cell responses. A major challenge for both HIV cure and remission strategies is to elicit HIV-specific CD8+ T cell responses superior to that elicited by natural infection in terms of response kinetics, magnitude, breadth, viral suppressive capacity, and tissue localization. Addressing these issues will be critical to the success of HIV cure and remission attempts.